Analysis of Doberman Pinscher and Toy Poodle samples with targeted next-generation sequencing - Arizmendi, Analía (2023)
Next-generation sequencing (NGS) technologies have enabled the identification of many causal variants of genetic disorders, the development of parentage tests and the analysis of multiple traits in domestic animals. In this study, we evaluated the performance of a Canine Targeted Genotyping-by-Sequencing (GBS) custom panel (Thermo Fisher Scientific, Waltham, Ma, USA) in a cohort of 95 dog DNA samples, comprising 76 Doberman Pinschers and 19 Toy Poodles from Argentina. The used panel included 383 targets (228 parentage SNVs, 137 genetic disorder markers and 18 trait markers). While paternity analysis showed correct duo (97.4%; LOD > 2.98E+13) and trio (100%; LOD > 2.20E+15) parentage assignment, the panel resulted still insufficient for excluding close relatives in inbred populations. In this sense, close relatives were wrongly assigned as parents in 12.6% of duos and 0.3% of trios. We detected 17 polymorphic markers (genetic disorders, n = 4; hair type, n = 3; coat color, n = 10) and estimated their allele frequencies in the studied breeds. The accuracy of targeted GBS results were evaluated for three markers that were associated with Progressive rod-cone degeneration, von Willebrand disease type 1 and dilated cardiomyopathy by pyrosequencing and Sanger sequencing genotyping, showing 94–100% concordance among assays. The targeted GBS custom panel resulted cost-effective strategy to study the prevalence of genetic disorders and traits in a large number of samples and to analyze genetic interactions between previously reported variants. Once assays based on AgriSeq technology were standardized, their uses are a good strategy for large-scale routine genetic evaluation of animal populations.